Taxonomic composition of the latest Carboniferous–earliest Permian smaller foraminifers in the Sanandaj-Sirjan Zone, Iran: New insights about palaeobiogeography, palaeoclimate and paleoecology of the northern margin of the Palaeotethys. (15th May 2020) - Fassihi, Shirin; Vachard, Daniel; Esfahani, Fariba Shirezadeh
Graphical abstract: Highlights: During the latest Gzhelian–Asselian Iran was located at the northern margin of the Palaeotethys. The studied assemblage is comparable to other areas in the Peri-Tethyan realm. This assemblage indicates the low latitude position with the warm and humid conditions. Abstract: The taxonomic diversity of smaller foraminiferal faunas of the uppermost Carboniferous–lowermost Permian (upper Gzhelian–lower Asselian interval) has been accurately investigated in the Sanandaj-Sirjan Zone, Iran. They predominantly contain three foraminiferal classes: Fusulinata, Miliolata and Nodosariata, and six orders: Tuberitinida, Earlandiida, Archaediscida, Endothyrida, Cornuspirida, and Nodosariida. The presence of some remarkable taxa in palaeobiogeography such as Hemidiscus carnicus, that is reported for the first time in Iran, along with Rectogordius is noticeable. Furthermore, these smaller foraminifers are associated with significant fusulinid genera including Praepseudofusulina, " Nonpseudofusulina ", Pseudoschwagerina, and " Schellwienia ?", which indicated that during the latest Gzhelian–Asselian, the Sanandaj-Sirjan Zone was in the northern margin of the Palaeotethys, in a relatively low latitudinal position (ca. 30°S), with warm and humid conditions. This claim can also be evidenced by the presence of sandstones with high degree of chemical weathering, together with the limonite accompanied with a palaeosol in the Upper Carboniferous strata. The presence of a red earthy laterite with lenses of pisolitic bauxite along with a piece of fossil wood in the lowermost Permian beds, confirms the Peri-Tethyan position of the Sanandaj-Sirjan Zone during this period. This study also shows that the first appearance of Frondicularia in the Iranian material, that is the latest Gzhelian–early Asselian, is probably older than what is argued in materials from north-central Siberia (Late Permian and Triassic) and Germany (Sakmarian to Anisian, up to the Jurassic).